Montessori game on toothbrushing knowledge and behaviour in elementary school children - Nurzain, Jian; Dewi, Tita Kartika; Tiana, Mita (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background: One of the places where many bacteria are found is the oral cavity. Influenced by temperature, humidity, and food availability. Knowledge of dental and oral health should be given from an early age because children begin to understand the importance of oral and dental health, which is strongly influenced by knowledge and behavior. Brushing teeth in children with a frequency that is not optimal can be caused because children are not accustomed to brushing teeth early by parents. To be done with fun, learning can be given with montessori games to improve children's knowledge and behavior. Objective: To determine the effect of the montessori brushing game method on increasing knowledge and brushing behavior of grade I students at MI Darul Khoer Wanayasa, Purwakarta Regency. Method: Design using quantitative analytics with one group pre-test and post-test design research design. The type of research used is the Wilcoxon test. Results: Students had knowledge and behavior of brushing teeth with less category 54.6% before the Montessori game method and after the Montessori game method 63.8% of children experienced an increase in knowledge and behavior of brushing teeth with a good category with Asymp.sign (2-tailed) scores of 0.000 < 0.05. Conclusion: There is an influence of Montessori game method on knowledge and behavior of brushing teeth in in elementary school children.